The rhetoric of digressions : Revelation 7:1-17 and 10:1-11:13 and ancient communication - Perry, Peter S., 1971- (T bingen, Germany : Mohr Siebeck, 2009)
"... analyzes Revelation 7:1-17 and Revelation 10:1-11:13 - interruptions in the seals and trumpets - in light of digressions in ancient rhetorical theory and practice."--Page [4] of printed paper wrapper.
Introduction: Experiencing Rev 7:1-17 and Rev 10:1-11:13 -- On structure and methodology -- Discontinuity and continuity in Revelation 7 and Revelation 10-11 -- Digressions in theory -- Digressions in practice -- Revelation 7:1-17 and Revelation 10:1-11:13 as digressions -- Conclusions and trajectories.
Slightly revised version of the author's thesis (Ph. D.)--Lutheran School of Theology, Chicago, 2008.
Includes bibliographical references (p. [263]-276) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Digression (Rhetoric); Rhetoric in the Bible